2020
DOI: 10.1155/2020/5710281
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Patients with Uncontrolled Blood Pressure at an Urban Hospital in Hanoi, Vietnam

Abstract: Great efforts to advance the diagnosis and treatment of hypertension for controlling hypertension have been made; however, the rates of uncontrolled blood pressure are still high. This study explored the rate of uncontrolled hypertension in patients with hypertension managed in an urban hospital of Vietnam and identified associated factors. A cross-sectional survey was performed from August to October 2019 among hypertensive patients at an urban hospital in Hanoi, Vietnam. Blood pressure was evaluated at the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“… n=17,199, M age = 44 years (range=25–64) National Men (24.5%) and Women (17.5%) were current smokers. Men (25.1%) and Women (15.8%) did not drink alcohol Traditional: Alcohol consumption, tobacco cessation Nguyen et al 52 (2020) Vietnam To explore the rate of uncontrolled hypertension and identified associated factors n=220 Hospital, urban area Did not smoke (87.7%), alcohol drinkers (28.6%), overweight/obesity (58%), did not adhere to medication (99.6%), did not follow a low-salt diet (50.5%), exercised regularly (85.0%) Traditional: Tobacco cessation, Alcohol consumption, bodyweight management, medication adherence, dietary intake, physical exercise Ko-Ko-Zaw et al 53 (2011) Myanmar To determine the prevalence of hypertension and its associated factors n=4616 ≥20 National Medication consumption (32%), current smokers (24.9%), alcohol drinkers (47.1%), moderate physical activity (47%), overweight (29.9%), obese (11.8%) Traditional: Medication adherence, tobacco cessation, alcohol consumption, physical exercise, bodyweight management Han et al 54 (2015) Myanmar To determine the prevalence of the adherence and to identify the factors related to medication adherence among hypertensive patients n=216, M age= 52.8 years Hospital, Urban area Poor medication adherence (49.1%) Traditional: Medication adherence, Oo et al 55 (2018) Myanmar To describe the relationships between personal and environmental factors and health behaviors in persons with hypertension n=104, M age= 53.27 years (range= 21 to 80) Urban area Moderate level of health behaviors (70.59 ± 12.39) Unspecified Haung et al 56 (2020) Myanmar To identify the prevalence of self-care behaviors and their associated factors among hypertensive patients n=410 M age= 55.4 years (range =30–70) Rural area Did not adhere to medication (75.9%), low diet quality (62.2%), inadequate physical activity (75.1%), poor bodyweight management (90.5%), smoking (49.8%), did not drink alcohol (97.8%) Traditional: Medication adherence, dietary intake, physical exercise, bodyweight management, tobacco cessation, and al...…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“… n=17,199, M age = 44 years (range=25–64) National Men (24.5%) and Women (17.5%) were current smokers. Men (25.1%) and Women (15.8%) did not drink alcohol Traditional: Alcohol consumption, tobacco cessation Nguyen et al 52 (2020) Vietnam To explore the rate of uncontrolled hypertension and identified associated factors n=220 Hospital, urban area Did not smoke (87.7%), alcohol drinkers (28.6%), overweight/obesity (58%), did not adhere to medication (99.6%), did not follow a low-salt diet (50.5%), exercised regularly (85.0%) Traditional: Tobacco cessation, Alcohol consumption, bodyweight management, medication adherence, dietary intake, physical exercise Ko-Ko-Zaw et al 53 (2011) Myanmar To determine the prevalence of hypertension and its associated factors n=4616 ≥20 National Medication consumption (32%), current smokers (24.9%), alcohol drinkers (47.1%), moderate physical activity (47%), overweight (29.9%), obese (11.8%) Traditional: Medication adherence, tobacco cessation, alcohol consumption, physical exercise, bodyweight management Han et al 54 (2015) Myanmar To determine the prevalence of the adherence and to identify the factors related to medication adherence among hypertensive patients n=216, M age= 52.8 years Hospital, Urban area Poor medication adherence (49.1%) Traditional: Medication adherence, Oo et al 55 (2018) Myanmar To describe the relationships between personal and environmental factors and health behaviors in persons with hypertension n=104, M age= 53.27 years (range= 21 to 80) Urban area Moderate level of health behaviors (70.59 ± 12.39) Unspecified Haung et al 56 (2020) Myanmar To identify the prevalence of self-care behaviors and their associated factors among hypertensive patients n=410 M age= 55.4 years (range =30–70) Rural area Did not adhere to medication (75.9%), low diet quality (62.2%), inadequate physical activity (75.1%), poor bodyweight management (90.5%), smoking (49.8%), did not drink alcohol (97.8%) Traditional: Medication adherence, dietary intake, physical exercise, bodyweight management, tobacco cessation, and al...…”
Section: Methodsmentioning
confidence: 99%
“…In the quantitative and mixed-method studies, body weight management (29 studies 20 , 24 , 25 , 29 , 30 , 33 , 36 , 39–50 , 52 , 53 , 56–62 , 64 ) and physical exercise (22 studies 21 , 22 , 24 , 30–33 , 35 , 38 , 40–43 , 45 , 47 , 52 , 53 , 56 , 57 , 60 , 61 , 75 ) were the most reported, whereas in the qualitative studies, medication adherence and diet intake was the most reported self-care practice. In addition, a few studies described alternative self-care management methods such as stress-relieving methods (6 studies 35 , 40 , 60 , 66 , 68 , 75 ), sleep and rest (2 studies 68 , 74 ), and spiritual fulfilment was described in one study.…”
Section: Self-care and Lifestyle Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Systolic hypertension, especially isolated (ISH), is common in older people aged ≥65 years and is a major risk factor for stroke and heart attack regardless of gender or ethnicity, and effective control of SBP is associated with a significant reduction in the incidence of these complications (Chrysant, 2018). Poorly controlled hypertension is widespread in Vietnam according to previous studies (Nguyen, 2020). According to the JNC 8 Blood Pressure Guidelines, for patients 60 years of age or older, it is recommended that they start drug therapy to lower their SBP to 150 mm Hg and diastolic blood pressure (DBP) <90 mm Hg, and in case of concomitant diabetes or chronic kidney disease (CKD), SBP should remain <140 mm Hg and DBP <90 mm Hg (Burns et al, 2019).…”
Section: Introductionmentioning
confidence: 99%